Recent applications of β-cyclodextrin in selective adsorption of pesticides, heavy metals, and organic pollutants from water samples: Mini review - Xiang Chuin, Lim; Kamaruzaman, Sazlinda; Mangala Praveena, Sarva; Yahaya, Noorfatimah (Elsevier Inc., 2024)
Heavy metals, pesticides, dyes, drugs, and organic micropollutants show significant threats to both the environment and life on Earth. Considering their presence in water sources, it becomes imperative to identify an efficient and environmentally friendly approach for their removal. This review highlights the prevalent use of the cost-effective and dependable adsorption method across various studies. The supramolecular β-CD, with its macrocyclic structure, offers an inner cavity and surface for adsorption through electrostatic interactions, hydrogen bonding, and weak van der Waals’ forces of attraction. Most β-CD-based adsorbents exhibit pseudo-second-order kinetics and fit to the Langmuir isotherm, suggesting monolayer and homogeneous chemisorption. Host-guest chemistry, inherent to supramolecular macrocycles, contributes to a comprehensive understanding of adsorption processes. Within this review, the kinetic models, isotherm models, and thermodynamic are analyzed. Additionally, optimization factors such as initial analyte concentration, pH, contact time, and adsorbent dosages are thoroughly explored.